Juridical Analysis of a District Court Decision in a Case of Persecution Precipitated by Verbal Provocation in Palangka Raya City (No.109/Pid.B/2024/Pn.Plk) - Sitorus, Esra Basaulina; Kristanto, Kiki; Dewi, Yurika F. (Journal of Law, Politic and Humanities, 2025)
This research aims to analyse in depth the juridical aspects in the Palangka Raya District Court Decision Number: 109/Pid.B/2024/Pn.Plk related to persecution cases triggered by verbal provocation. The focus of the research is on the legal considerations used by the judge in deciding the case, as well as how the verbal provocation factor is used as the basis for imposing criminal sanctions. The research method used is normative juridical with the approach of analysing court decisions, literature studies on the Criminal Code (KUHP), and studies of criminal law doctrines related to criminal liability and factors that trigger criminal acts. The results showed that although verbal provocation by the victim was the trigger for the defendant's act of maltreatment, the court decided that the defendant's actions had exceeded proportional limits. The judge emphasised that verbal provocation cannot remove the element of culpability in the crime of maltreatment, although it can be taken into consideration in mitigating the punishment. This decision reflects the principles of fairness and proportionality in law enforcement, where judges must carefully weigh the triggering factors and the degree of guilt of the defendant. This research also identified that the verdict was in line with Article 351 of the Criminal Code on maltreatment, however the judge did not provide significant leniency because the defendant's actions were considered excessive.